Control of Hammerstein nonlinear system - Taufer, Ivan; Drábek, Oldřich (Univerzita Pardubice, 1995)
The paper deals with the control of a nonlinear plant with the quadratic steady-state characteristics. The plant is described by Hemmarstein model and controlled by a deadbeat controller. The controller is designed by the classical complex area method. The choice of a sampling period T in the dependence of the plant character (with minimum or nonminimum phase) and of the model plant parameters is presented. The choice of T is based on an admitted actuator range and on the keeping the deadbeat – strong version criterion condition. Simulation examples are presented.